A novel functionalized pillar[5]arene-based selective amino acid sensor for l-tryptophan. Issue 2 (17th November 2016) - Wei, Tai-Bao; Chen, Jin-Fa; Cheng, Xiao-Bin; Li, Hui; Han, Bing-Bing; Zhang, You-Ming; Yao, Hong; Lin, Qi
Abstract : The sensing mechanism of the sensorBTAP5 forl -Trp. Abstract : A novell -tryptophan (l -Trp) fluorescent sensor (BTAP5) based on a functionalized pillar[5]arene has been developed. The sensor BTAP5 exhibits high selectivity and sensitivity (2.83 × 10 −7 M) towardsl -Trp in H2 O/DMSO (7 : 3, v/v) solution. The recognition mechanism was studied by 1 H NMR, electrospray ionization mass spectrometry and 2D NOESY.